2021
DOI: 10.3390/ijms222111970
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin and Levofloxacin as Potential Drugs in Genitourinary Cancer Treatment—The Effect of Dose–Response on 2D and 3D Cell Cultures

Abstract: Introduction: Introducing new drugs for clinical application is a very difficult, long, drawn-out, and costly process, which is why drug repositioning is increasingly gaining in importance. The aim of this study was to analyze the cytotoxic properties of ciprofloxacin and levofloxacin on bladder and prostate cell lines in vitro. Methods: Bladder and prostate cancer cell lines together with their non-malignant counterparts were used in this study. In order to evaluate the cytotoxic effect of both drugs on teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…The effect of ciprofloxacin used in high concentrations (about 200 µg/mL) on the bladder and prostate cancer cell lines has been demonstrated in in vitro studies [ 6 , 33 ]. In addition, a comparison of the cytotoxic action of ciprofloxacin and levofloxacin on prostate and bladder cancer indicated a greater anticancer potential of ciprofloxacin [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ciprofloxacin used in high concentrations (about 200 µg/mL) on the bladder and prostate cancer cell lines has been demonstrated in in vitro studies [ 6 , 33 ]. In addition, a comparison of the cytotoxic action of ciprofloxacin and levofloxacin on prostate and bladder cancer indicated a greater anticancer potential of ciprofloxacin [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we tested both drugs on a non-malignant uroepithelial cell line. Our results showed that both tested drugs were more effective against cancer cell lines which were more pronounced in 3D culture ( 62 ).…”
Section: Resultsmentioning
confidence: 72%
“…Levofloxacin, compared to ciprofloxacin, was more effective against the DU-145 cell line after a 24-h incubation, while after 48 h the situation was opposite. In this study, the advantage of both drugs over cancer cells was demonstrated ( 62 ). In the case of norfloxacin, it was shown that prostate cancer cells were the most resistant to this drug among all tested cancer cell lines.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations